Association of bullying on happiness at school: evidence from Thailand’s national school-based survey - Aubdul Aunampai (2022)
This study aims to investigate the association of bullying victimization of primary school students with their happiness in urban and rural areas of Thailand. A nationally representative survey from Thailand Healthy School Data 2017 was employed. A total of 7,825 students (age 6 to 12 years) from 160 schools in 9 regions were included in the analysis. Multistage probability random sampling was applied to select students enrolled and collected data through face-to-face interviews. About 49.7% of students had been bullied. Bullying victimization was higher among males (52.0%) and younger students. Bullying was also associated with urban/rural (x2 = 5.3, p = 0.021). Students who had been bullied were 28.0% less likely to be happy (p 0.000; CI 0.647–0.810). Bullying victimization has a significant negative effect on students’ happiness. The findings suggest that specific action should be taken by entities which directly contribute to the implementation of the education system in Thailand.